2004
DOI: 10.1128/jb.186.7.2195-2199.2004
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus anthracisandBacillus cereusPcrA Helicases Can Support DNA Unwinding and In Vitro Rolling-Circle Replication of Plasmid pT181 ofStaphylococcus aureus

Abstract: Replication of rolling-circle replicating (RCR) plasmids in gram-positive bacteria requires the unwinding of initiator protein-nicked plasmid DNA by the PcrA helicase. In this report, we demonstrate that heterologous PcrA helicases from Bacillus anthracis and Bacillus cereus are capable of unwinding Staphylococcus aureus plasmid pT181 from the initiator-generated nick and promoting in vitro replication of the plasmid. These helicases also physically interact with the RepC initiator protein of pT181. The abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 37 publications
0
31
1
Order By: Relevance
“…The failure to establish pT181 in S. pneumoniae suggested that this staphylococcal plasmid was unable to replicate in this bacterium, in agreement with the apparent inability of the RepCPcrA Spn complex to efficiently unwind the pT181 DNA. In contrast to these results, heterologous PcrA helicases from Bacillus cereus PcrA Bcer and Bacillus anthracis PcrA Ban (two species in which the pT181 replicon could be established) are known to extensively unwind RepC-nicked pT181 DNA and support pT181 replication in vitro (3). We propose that a functional interaction between the plasmid-encoded replication initiator protein and the host PcrA helicase is essential for establishment and replication of RCR plasmids in gram-positive bacteria.…”
contrasting
confidence: 42%
See 1 more Smart Citation
“…The failure to establish pT181 in S. pneumoniae suggested that this staphylococcal plasmid was unable to replicate in this bacterium, in agreement with the apparent inability of the RepCPcrA Spn complex to efficiently unwind the pT181 DNA. In contrast to these results, heterologous PcrA helicases from Bacillus cereus PcrA Bcer and Bacillus anthracis PcrA Ban (two species in which the pT181 replicon could be established) are known to extensively unwind RepC-nicked pT181 DNA and support pT181 replication in vitro (3). We propose that a functional interaction between the plasmid-encoded replication initiator protein and the host PcrA helicase is essential for establishment and replication of RCR plasmids in gram-positive bacteria.…”
contrasting
confidence: 42%
“…The transcriptional terminator of the cat gene and the transcriptional terminator proposed to attenuate transcription of radC are indicated by hairpin symbols. (3,9,34), the ATPase activity of His-PcrA Spn was significantly stimulated by addition of ssDNA to the reaction mixtures (Fig. 4).…”
mentioning
confidence: 99%
“…poly(dT) 4 3.06 袭 0.65 23.3 袭 0.2 poly(dT) 6 1.99 袭 0.38 16.4 袭 0.1 poly(dT) 10 0.37 袭 0.03 32.7 袭 0.4 poly(dT) 13 0.16 袭 0.03 27.9 袭 0.1 poly(dT) 18 0.059 袭 0.003 29.4 袭 0.3 poly(dT) 23 0.045 袭 0.004 24.7 袭 0.5 poly(dT) 40 0 (Fig. 7A) showed a nonsigmoidal increase in ATPase rate with the protein concentration in the range tested (20 nM to 500 nM), indicating the absence of any significant cooperativity between protein molecules.…”
Section: Resultsmentioning
confidence: 99%
“…B. stearothermophilus PcrA shows a strong preference for double-stranded substrates containing a 3袌 single-stranded tail over substrates containing a 5袌 singlestranded tail (19). Interestingly, Bacillus anthracis, Bacillus cereus, and S. aureus PcrAs were equally active as 5袌-3袌 helicases and 3袌-5袌 helicases (4,48).…”
mentioning
confidence: 99%
“…In all these strains, the role of PcrA in RCR has been studied using the broad host range pT181 plasmid as a reference (31,174). A clear interaction of the helicase with the replication initiation protein was successfully observed by pull-down for all three PcrAs.…”
Section: Role Of Superfamily Group 1 Helicases and Their Interaction mentioning
confidence: 99%